Asking a Chatbot for COVID-19 Food and Nutrition - Fahmi Fahmi; Yusrandi Yusrandi; Aji P. Wibawa; Ming Foey Teng; Purnawansyah Purnawansyah (Universitas Negeri Malang, 2021)
Coronavirus 19 (COVID-19) is a disease caused by a new coronavirus called severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2; previously known as 2019-nCoV). On March 11, 2020, WHO declared COVID-19 a global pandemic, the first pandemic since H1N1 influenza was declared a pandemic in 2009. The disease has hit almost every country in the world and so far, no medicine nor antiviral was found. In some countries where the death rate is high, the number of patients continues to increase. On May 20, 2020, the number of patients exceeded 4.8 million and the toll is 318,000 (6.6 percent). Although the number of new patients in many countries declined after the access rights lockdown (lockdown), the second attack returned to the area where the first attack occurred. The COVID-19 case in Indonesia still shows an increasing trend even though various efforts have been made by the state and society. This research is intended to discuss us regarding the use of chatbots to provide guidance on food and nutrition during the COVID-19 pandemic. The results showed that a review of maintaining a healthy lifestyle by adhering to health protocol during the pandemic of COVID-19, shows that the higher the rating, the more effective it is to reduce the transmission of the corona virus in the future.